PERBAIKAN TATA LETAK PASAR INDUK TRADISIONAL DI SANGATTA DENGAN METODE MARKET BASKET ANALYSIS (MBA) - Indra Wahyudi, Anwar Arifin (RJABM (Research Journal of Accounting and Business Management), 2021)
ABSTRACTThe customer is one of the goals of the market. One of the factors that influence consumer satisfaction is the arrangement of products/products. An attractive display becomes the face of the market itself. The Traditional Main Market in Sangatta is a market that is satisfied with consumers. So far, the product arrangement of the Traditional Main Market in Sangatta has only been based on the intuition of the market management, while the wide market area causes consumers to feel tired when shopping.The Market Basket Analysis method aims to determine what products are usually purchased by consumers at the same time. In addition, the application of this method can provide convenience for consumers in shopping, because goods that are usually purchased simultaneously are nearby. In addition, it can improve efficiency in conducting promotions. Products purchased  should not be produced simultaneously,  promoting one product can increase sales of other products that are usually purchased simultaneouslyThis study uses the Market Basket Analysis (MBA) method. Product information that dominates sales can be used as a reference to determine consumer habits in making purchases. The habit in question is any product that consumers buy at the same time. The use of Market Basket Analysis (MBA) is expected to cause impulse buying/purchases that were not planned. In addition to using Market Basket Analysis (MBA), Activity Relationship Chart (ARC) is also used as a tool to get layout results that are by consumer habits in shopping and with government regulations. Keywords : Product layout, Market basket analysis, Activity relationship chart.